Tribo-dynamics Analysis of Satellite-bone Multi-axis Linkage System - Xu, Jimin; Hong, Honglun; Yuan, Xiaoyang; Zhao, Zhiming (Journal of Applied Nonlinear Dynamics, 2026)
Friction torque is the most important factor that influences stability and precision of multi-axis linkage system during low-speed running. It is primarily related to shafting structure, external load, motion state and other factors, and presents highly nonlinear characteristics. In this paper, satellite-bone multi-axis linkage system in microgravity environment is taken as the research object to focus on the coupling tribo-dynamics issues of influencing system’s precision. The shafting structural features of two degrees of freedom (2-DOF) vertical-axis turntable, source of friction torque and coating antifriction technology are studied. The corresponding tribo-dynamics model is established. The model shows motion process of multi-axis linkage system is a coupling process of tribology and dynamics. In order to eliminate the effect of friction torque fluctuations, friction compensation based on LuGre friction model is introduced. Then tracking precision of the visual axis is about 40'' (large movement range). For the imperfect situations with friction compensation, local actuator is introduced to combine with wide-range basic multi-axis system to realize the accurate movement within small range. Then the tracking precision of visual axis is expected to reach about 2'' to 4'' (small movement rang).